Knowledge Sharing Strategies for Large Complex Building Projects - Bektaş, Esra (A+BE | Architecture and the Built Environment, 2013)
The construction industry is a project-based sector with a myriad of actors such as architects, construction companies, consultants, producers of building materials (Anumba et al., 2005). The interaction between the project partners is often quite limited, which leads to insufficient knowledge sharing during the project and knowledge being unavailable for reuse (Fruchter et al. 2002). The result can be a considerable amount of extra work, delays and cost overruns. Design outcomes that are supposed to function as boundary objects across different disciplines can lead to misinterpretation of requirements, project content and objectives. In this research, knowledge is seen as resulting from social interactions; knowledge resides in communities and it is generated through social relationships (Wenger 1998, Olsson et al. 2008). Knowledge is often tacit, intangible and context-dependent and it is articulated in the changing responsibilities, roles, attitudes and values that are present in the work environment (Bresnen et al., 2003). In a project environment, knowledge enables individuals to solve problems, take decisions, and apply these decisions to actions. In order to achieve a shared understanding and minimize the misunderstanding and misinterpretations among project actors, it is necessary to share knowledge (Fong 2003). Sharing knowledge is particularly crucial in large complex building projects (LCBPs) in order to accelerate the building process, improve architectural quality and prevent mistakes or undesirable results. However, knowledge sharing is often hampered through professional or organizational boundaries or contractual concerns. When knowledge is seen as an organizational asset, there is little willingness among project organizations to share their knowledge. Individual people may recognize the need to promote knowledge sharing throughout the project, but typically there is no deliberate strategy agreed by all project partners to address knowledge sharing. In the literature, two main approaches on knowledge sharing can be distinguished, an object or content -oriented perspective and a community-oriented perspective. In the object perspective, technology is seen as a medium to store and share knowledge. The limitations of this perspective are that social processes and tacit knowledge are not adequately supported and there has generally been a slow adoption of such technology in design practices. The community perspective prevents these problems by allowing for the natural and informal formation of communities, however, communities can become largely independent and unconnected, which makes it more difficult to entice them towards a certain strategic direction. Since both approaches have their limitations, this thesis proposes a holistic framework for knowledge sharing in LCBPs drawing on concepts by Mintzberg (1973) and Activity Theory. Mintzberg’s concepts are used to discuss the type of implementation (top-down, bottom-up), and the origin of the strategies (deliberate/emergent/(un)realized). For analysing the content and effect of each strategy, concepts from Activity Theory (tools, subject, object, rules, community, and division of labour) are used. The proposed model, the Knowledge Diamond, consists of four dimensions for analysing and designing knowledge sharing strategies for LCBPs. Three of these were inspired by Activity Theory, namely tools, procedures, and social practices, while a fourth emerged as a crucial dimension in this thesis: physical settings. This framework was used to examine knowledge sharing strategies in a comparative analysis of two large complex building projects. Based on rich data from observations, documents and interview, the origins, the development and the effect of both forms of knowledge sharing environments are investigated. The first part of the analysis sheds new light on the possibilities of knowledge sharing in large complex building project. The unique, temporary, and complex nature of such projects has often been reported as a potential barrier to investing knowledge sharing. However, this analysis highlighted that the while the location is unique, the underlying challenges are typically not, and although projects are per definition temporary, these large, complex projects often last for a decade. Investing in knowledge sharing is therefore possible and worth the effort, and with respect to complexity more needed than those involved are aware of. In the second part of the empirical data analysis, the knowledge sharing strategies inuse in the two cases were examined. The first case represents a people-oriented approach using collocated open plan offices for the entire design team; the second case represents a tool-oriented approach drawing on a Building Information Model (BIM). The co-located offices provided the physical setting for knowledge sharing, but it not planned as a conscious strategy and so was mainly regarded as sharing the same office floor and was not used to its full potential. Physical boundaries remained between subteams and interaction was restricted to the level of project managers. In the second case, the implementation of a BIM represented a bottom-up and emergent strategy that embraced digital technologies for specific problems. The analysis showed that there was limited understanding about requirements and implication of changes in the design processes. Introduced through a bottom-up emergent strategy without commitment from all project partners, it was not possible to utilize the potential benefits of a BIM system for the overall design team. The analysis also revealed that what practitioners referred to as a BIM, was not a true BIM implementation, thereby indicating that digital concepts are still not completely clear in practice. This comparative analysis of two cases led to several conclusions: Irrespective of whether a tool or people-oriented approach is used, there will be emerging strategies with which people try to address problems caused by limited knowledge sharing. The physical setting can play a major role in supporting interaction. Designers and managers will make intentional or spontaneous use of the possibilities that their physical setting affords, even though tools are available that can facilitate distributed work. Thus, tool implementations do not make physical settings obsolete. Tools provide a technological infrastructure such as creating virtual proximity, handling design and criteria changes, enhancing design representation, or dealing with changes in personnel. However, there is no magic want that cures all problems and challenges of LCBPs. Procedures refer to formal and informal rules about knowledge sharing. Such rules are important means of creating shared expectations and information exchange, however, procedures can only guide but not dictate the actual behaviour of actors in regard to knowledge sharing. Social practices form the social infrastructure that enables and facilitates knowledge sharing through the physical setting, tools, and procedures. However, if the project culture has emerged intuitively, these practices may involve rather limited sharing behaviour at various levels (i.e. executive, managerial, and technical). Through my research and recommendations, I have attempted to offer fresh insights to practitioners about the value and necessity of knowledge sharing in large complex building projects. The framework of the Knowledge Diamond is not intended as a magic cure, but it can serve as a guideline for enhancing knowledge sharing by paying explicit attention to all four dimensions and taking advantages of new technologies such as BIM and 3D models. Although the insights of this research are based on only two cases, the conclusions were confirmed by a panel of experts who confirmed similarities with their own experience. This study also contributed to the literature on knowledge sharing and project management. The Knowledge Diamond can help to conceptualise knowledge sharing at both the inter-organizational and cross-disciplinary level. It can also form the basis for further theory development about work in project-based settings and help to define new project management methodologies.